Work-family balance in Malaysia: Does work-family policy make a difference? - Hassan, Zaiton; Dollard, Maureen F.; Winefield, Anthony H. (Universiti Malaysia Sarawak, 2008)
In Western literature, work-family policy is seen as an important agenda to address work-family balance issues. However, there is a lack of evidence on the relationship between work-family policy and work-family balance in Eastern cultures. The aim of this study was to advance the understanding of work-family policy and its relationship to work-family balance (i.e., conflict and enrichment) in Sarawak, East Malaysia. A sample of 506 employees from three public and three private sector organizations was surveyed twice in three months. By way of questionnaires, participants completed measures of work-family policy by Haar and Spell (2003), work-family conflict by Carlson et al., (2000) and work-family enrichment by Carlson et al., (2006).